DESIGN EXAMPLE OF STORAGE SYSTEM USING THE LOGISTICS PRINCIPLES (Perner's Contacts, 2018)
The paper presents an example of design a storage system using the logistics principles - system approach, coordination, planning, algorithmic thinking and global optimization. In this case, storage is understood as a subsystem of the logistics system and too as a process. The design process of storage system is the application of design logistics systems. This process consists of several phases: project identification, design process paradigm selection, system analysis, logistics synthesis and project evaluation. These steps are modified for the design of the storage system. The example of a storage system design is expressed as a flowchart. The presented design process and flowchart can be further refined and supplemented depending on the problems, which can be identified in the design process.
Keywords: design, storage system